Quality of Life: A Case Study of the City of Benghazi – Pilot Study (Comprehensive Journal of Science, 2025)
This study aims to explore the indicators of urban quality of life in the city of Benghazi, as a fundamental element in achieving residents’ satisfaction and developing an integrated urban environment. It adopts a descriptive-analytical approach through a questionnaire conducted with 83 participants of various ages and professions.The results revealed discrepancies in the availability of environmental, physical, and social indicators across the city—such as green spaces, lighting, infrastructure, and transportation—highlighting the need for urban planning interventions to enhance quality of life.Key recommendations include: Strengthening community participation in urban planning. Enhancing infrastructure and public services. Improving transportation, mobility, and public amenities. Promoting environmental and planning sustainability.This study is considered one of the first initiatives in Libya to highlight the concept of urban quality of life as a central pillar of sustainable urban development.
Keywords: quality of life; urban design; urban planning; Benghazi city.